Nexus between Capital Expenditure and Economic Growth in Indonesia in the Covid-19 Pandemic - Fadhilah, Hanifah Zulfa; Chandra, Herlina Aria; Wahyuningsih, Merliana; Badrudin, Rudy (Journal of Business & Banking, 2022)
This study aimed to determine the relationship between capital expenditure and the Covid-19 pandemic on economic growth in Indonesia. This study used a sample of all provinces in Indonesia, consisting of 34 provinces in 2019-2021. It analysed the data by using an Analysist Covariate or ANCOVA. The results showed that capital expenditure had no effect on economic growth while the Covid-19 pandemic had a positive effect on economic growth. The Covid-19 pandemic in this study was initially formulated that the Covid-19 pandemic had a negative impact, but the results of the study said otherwise. The positive influence of the Covid-19 pandemic is due to the digitalization of the economy. Capital expenditure issued by the government during the pandemic has not been able to increase economic growth. Therefore, the government must consider the allocation of capital expenditures in the APBD and supervise the implementation of the APBD, especially during the Covid-19 pandemic.